2023
DOI: 10.1038/s41467-023-39731-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining amino acid PET and MRI imaging increases accuracy to define malignant areas in adult glioma

Abstract: Accurate determination of the extent and grade of adult-type diffuse gliomas is critical to patient management. In clinical practice, contrast-enhancing areas of diffuse gliomas in magnetic resonance imaging (MRI) sequences are usually used to target biopsy, surgery, and radiation therapy, but there can be discrepancies between these areas and the actual tumor extent. Here we show that adding 18F-fluoro-ethyl-tyrosine positron emission tomography (FET-PET) to MRI sequences accurately locates the most malignant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In clinical trials, contrast-enhanced areas of diffuse gliomas in MRI sequences are used as targets of biopsy, surgery, and radiation therapy, although there can be discrepancies between these areas and the actual tumor extent. The contrast-enhanced malignant 6b) [78]. Applications of PET/MRI to disease diagnosis and drug research have also been reported [82,83].…”
Section: Drug Sensitivity Analysismentioning
confidence: 92%
“…In clinical trials, contrast-enhanced areas of diffuse gliomas in MRI sequences are used as targets of biopsy, surgery, and radiation therapy, although there can be discrepancies between these areas and the actual tumor extent. The contrast-enhanced malignant 6b) [78]. Applications of PET/MRI to disease diagnosis and drug research have also been reported [82,83].…”
Section: Drug Sensitivity Analysismentioning
confidence: 92%
“… 2 Within diffuse gliomas, there is a positive correlation between PET uptake intensity and tumor grade ( Figure 1 ). 3 Overall, the majority of diffuse gliomas shows uptake of amino acid tracers with PET-positivity rates reported to be 70%–80% for grade 2 gliomas and around 90% of grade 3 and 4 gliomas, with oligodendrogliomas showing higher uptake values than astrocytomas. 4 So far, however, no data on amino acid PET imaging in patients exposed to IDH inhibitors are available.…”
mentioning
confidence: 95%
“…1 Due to its heterogeneity and complexity, orthotopic glioma imaging remains challenging, and the resolution of clinical imaging approaches is suboptimal. 2 Currently, fluorescence imaging (FI), especially emission in the second-near-infrared region (NIR-II, 1000−1700 nm), has garnered widespread attention in glioma diagnostics, intraoperative navigation and neurodegenerative diseases examination, with merits of high temporal-spatial resolution, deep penetration, and reduced tissue scattering. 3−7 Since clinical indocyanine green (ICG) cannot meet glioma imaging needs owing to its strong photobleaching and weak NIR-II tailed-emission, considerable effort has been dedicated to developing novel NIR-II emissive probes, including aggregation-induced emissive molecules, rare-earth based nanocrystals (NCs) and semiconducting NCs.…”
mentioning
confidence: 99%
“…Glioma represents one of the most common intracranial primary malignant tumors, characterized by poor prognosis, strong aggressiveness, and low survival rate . Due to its heterogeneity and complexity, orthotopic glioma imaging remains challenging, and the resolution of clinical imaging approaches is suboptimal . Currently, fluorescence imaging (FI), especially emission in the second-near-infrared region (NIR-II, 1000–1700 nm), has garnered widespread attention in glioma diagnostics, intraoperative navigation and neurodegenerative diseases examination, with merits of high temporal-spatial resolution, deep penetration, and reduced tissue scattering. Since clinical indocyanine green (ICG) cannot meet glioma imaging needs owing to its strong photobleaching and weak NIR-II tailed-emission, considerable effort has been dedicated to developing novel NIR-II emissive probes, including aggregation-induced emissive molecules, rare-earth based nanocrystals (NCs) and semiconducting NCs. Among them, semiconducting NCs emerge as a promising option due to their tunable luminescence, good stability, and straightforward functionalization. , However, well-developed NIR-II NCs normally contain toxic heavy elements such as PbS, PbS@CdS, and HgS, posing challenges for utilization in living organisms where even trace amounts are detrimental .…”
mentioning
confidence: 99%